Professional nurses’ perceptions regarding clinical competence of community service nurses in North West province, South Africa - Kholofelo L. Matlhaba (AOSIS, 2021)
Background: South African Nursing Council requires nurses who successfully complete their training to perform a year of community service before obtaining registration as professional nurses (Regulation 425). Community service for health professionals was introduced as a strategy to retain newly qualified professionals within the country. The premise is that community service for newly graduated nurses gives them the opportunity to develop skills and acquire knowledge critical in their professional development.